What cigarette price is required for smokers to attempt to quit smoking? Findings from the ITC Korea Waves 2 and 3 Survey. (22nd June 2015) - Park, Eun-Ja; Park, Susan; Cho, Sung-il; Kim, Yeol; Seo, Hong Gwan; Driezen, Pete; Quah, Anne C K; Fong, Geoffrey T
Abstract : Objectives: We assess the cigarette price that would motivate smokers to quit. We also explore the factors associated with the required price, including exposures to non-tax tobacco control policies. Methods: Cross-sectional analysis was conducted on data from 1257 male smokers, who participated in either Wave 2 or 3 of the ITC Korea Survey. Information was obtained on what cigarette price per pack would make them try to quit ('price to quit'). Tobit regression on log-transformed price and logistic regression on non-quitting were conducted to identify associated factors. Results: The median price to quit was KRW5854 (US5.31)/pack, given the current price of KRW2500 (US2.27)/pack. Younger age, higher education, lack of concern about the health effects of smoking, lack of quit attempts and more cigarettes consumed per day were related to a higher price needed for a quit attempt. Exposures to combinations of non-tax policies were significantly associated with lower price levels to be motivated to quit. Conclusions: Considering the large price increase required for quit attempts, tax policy needs to be combined with other policies, particularly for certain groups, such as heavy smokers. Strengthening non-tax policies is likely to facilitate greater responsiveness to tax policy.